PROSES BERPIKIR KREATIF BERDASARKAN KOMPONEN KREATIVITAS PEMECAHAN MASALAH SISWA PADA MATERI SPLDV - Naja, Ahmad Rifqi; Suharto, Suharto; Hobri, Hobri (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research aims to describe students’ thinking process based on creativity components of problem solving in linear equation systems with two variables. This research type is descriptive with qualitative approach. Data collection methods which were used are test and interview. This research subject are 4 students who randomly chosen from a class. Creativity components are fluency, flexibility, and novelty. Result of the research showed that 1 student fulfilled all of three components of creativity, 2 students only fulfilled flexibilty and fluency component and 1 student did not fulfill any of the creativity components. Keywords: Creative thinking process, creativity components of problem solving, linear equation systems with two variables